(untitled) (Third Sector Social Economic Review, 2022)
Public social assistance, which is one of the social policy tools, is used intensively in Turkey. The existence of many problems regarding the functioning of social assistance applications, which are determination of aid programs, criteria for benefiting, announcement and, are widely mentioned in the literature. In this study, it is aimed to develop solution proposals for these problems by examining the functioning of the social assistance application system, revealing its deficiencies and failing aspects. 8 manager surveys with municipalities, social assistance and solidarity foundation and also 210 beneficiary surveys with households, who are receiving social assistance and residing in rural area, were conducted by face-to-face interviews in Iğdır province. There is a lack of coordination among public institutions that provide aid and a lack of legislation in local governments. Although 95.2% of the beneficiaries are satisfied with the social assistance, only 17.1% of them find the social assistance sufficient. Common information system is needed, which can be used by the social assistance foundation and municipalities. It will be beneficial to include all public institutions and non-governmental organizations in this system. The adequacy status of social aids should be examined and improvements should be made according to the types of programs.